Work-life Balance and Employee Productivity a Case Study of Makerere University Business School Entrepreneurship, Innovation and Incubation Centre (M-eiic) Kampala - Immaculate Ivone Kayaga (Uganda Christian University, 2026)
At the Makerere University Business Schools Entrepreneurship Innovation and Incubation Centre we are exploring how work-life balance affects employee productivity. Its tricky space where innovators juggle multiple roles and we are looking at how things like flexible work arrangements and support systems can help them thrive. By understanding what works best we hope to help M-EIIC create policies that boost productivity and keep innovators happy and healthy.
Undergraduate